The Peter Pan Syndrome: Outcome of Helicopter Parenting - Chadha, Nidhi (International Journal of Psychosocial Rehabilitation, 2020)
The Peter Pan Syndrome can be understood as people with the body of an adult but the mind of a child. They don’t know how to or don’t want to stop being children and start being mothers or fathers when they are over 30 years old. The ‘Peter Pans’ of present society see the adult world as very problematic and glorify adolescence, which is why they want to stay in that state of privilege. Faulty parenting styles such as helicopter or over protecting parenting might encourage their children to enjoy childhood but fail to teach skills like budgeting, housecleaning or simple repair skills, and relationship maintenance behaviors which are crucial for adulthood. This research paper is qualitative in nature and tries to explore the phenomenon of Peter Pan syndrome and the crucial factors that may play a role in this Syndrome as there is scarcity of research on this phenomenon. Therefore, is quite imperative for child psychologists, school counselors, pediatrics and to help parents understand and realize importance of child rearing practices so that upcoming ‘overparenting epidemic’ can be curtailed.